Original article Epidermal growth factor receptor gene expression in high grade gliomas - Larysz, Dawid; Kula, Dorota; Kowal, Monika; Rudnik, Adam; Jarząb, Michał; Blamek, Sławomir; Bierzyńska-Macyszyn, Grażyna; Kowalska, Małgorzata; Bażowski, Piotr; Jarząb, Barbara (Folia Neuropathologica, 2011)
Background : Epidermal growth factor receptor (EGFR) gene amplification and protein expression in malignant gliomas (anaplastic astrocytoma, AA and glioblastoma, GBL) were suggested to be correlated with the degree of malignancy. Large deletions within the EGFR gene occur frequently in glioma patients. The aim of our study was to analyse EGFR gene expression by real-time PCR by three different amplicons located across the gene and relate it to the age of patients and EGFR mutation status. Material and methods : We analysed EGFR gene expression in 75 patients, median age 58 years (range 28-75), 52% of glioblastomas, 39% of anaplastic astrocytomas and 9% of low grade gliomas. EGFR expression was measured by real-time PCR, three amplicons located at exons 2-3, 13-14, and 17-18 junctions were analysed, gene expression was normalized by 18S RNA expression. EGFRvIII deletion was detected by RT-PCR. Results : EGFR was found to be expressed in 61.8% of brain gliomas, with strongly positive expression in 12.2% of them. We simultaneously analysed by RT-PCR the EGFRvIII status and found the deletion in 21.3% of tumours. In our group EGFRvIII mutation was significantly more frequent in patients older than 50 years of age (48.6%) than in younger patients (23.5%, p < 0.05). When only GBL patients were assessed, none of the patients younger than 50 years of age had EGFRvIII mutation, whereas in the older subgroup they constituted 36.67% of subjects. We observed that younger patients (below 50 yrs) had slightly lower EGFR expression in comparison to older patients, but this difference was not statistically significant. Conclusions : As nearly 1/3 of high grade gliomas do not demonstrate abnormal gene expression levels, EGFR status should be taken into account in any targeted therapy attempt. The significance of EGFR axis-related differences between young and old glioma patients and their impact on the prognosis warrant further study.